Is Doppler echocardiography useful for estimating left ventricular filling pressures in pediatric heart transplant recipients?. (16th July 2019) - Lunze, Fatima I.; Narciso, Ryan; Gauvreau, Kimberlee; Blume, Elizabeth D.; Colan, Steven D.; Singh, Tajinder P
Abstract: LV E/E′ ratio obtained using Doppler echocardiography is considered a surrogate for LV filling pressure in adults but has performed poorly in children. We hypothesized that LV E/E′ ratio Z ‐score, adjusted for age, will relate more strongly to LV filling pressures than LV E/E′ ratio in pediatric HT recipients. We analyzed 751 echocardiograms performed within 24 hours of a heart catheterization in 122 pediatric HT recipients (median age at HT 13 years, median 6 studies per patient). The primary end‐point was PCWP, assessed both as a continuous and a binary variable. Associations with LV E/E′ ratios and z ‐scores were assessed using generalized estimating equations models. PCWP, LV E/E′ ratios (using E′ from LV free wall, septum, and their average), and LV E/E′ ratio Z ‐scores, all declined over time after HT. LV E/E′ ratios and their Z ‐scores were significantly associated with PCWP assessed as a continuous variable ( P < 0.001 for all); however, the relationship was weak ( R 2 range, 0.083 to 0.121). LV E/E′ ratios and their Z ‐scores were also significantly associated with PCWP as a binary variable ( P < 0.001 for all) but with only modest ability to discriminate PCWP ≥15 mm Hg ( c ‐statistic range, 0.660 to 0.695). The association between LV E/E′ ratio and PCWP in pediatric HT recipients is modest. Using a LV E/E′ ratio Z ‐score did not result in significantly improved association with PCWP. Current Doppler echocardiographic methods are unreliable for estimating LV filling pressures in pediatric HT recipients.